Peran Guru Ngaji di Era Sustainable Development Goals (SDGs) (Studi Kasus di Desa Semat Tahunan Jepara) - Ahmad Saefudin; Nur Fitriyah (JURNAL INDO-ISLAMIKA, 2020)
The phenomenon of globalization has entered people's lives, including in Semat Village, Tahunan District, Jepara Regency. The indicator is the development of information technology tools and changes in people's attitudes and lifestyles that tend to follow modern styles. Even though, globalization has not discouraged people from participating in several activities that are in line with the SDGs target in the economic and education sectors, especially in efforts to end poverty and ensure inclusively and quality education. This study aims to emphasize the role of guru ngaji in promoting sustainable global development (SDGs) in the economic and educational domains. A crucial research question that will be answered is whether it is true that global phenomena can cause the younger generation to become increasingly dependent on technological tools and the gradual fading of the sense of solidarity among fellow communities.